ANALYSIS OF DEFENSE AND CYBER SECURITY IN AIRSPACE MANAGEMENT IN INDONESIA - Sudarto; Rina Dyahtaryani, Lidia; Trianto, Nanang (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
Air space management is a crucial aspect in maintaining the sovereignty of a country, including Indonesia. Along with the rapid development of information and communication technology, threats to cyber security are becoming increasingly significant. This research analyzes defense and cyber security efforts in air space management in Indonesia, with a focus on identifying threats, vulnerabilities, and implemented mitigation strategies. Through descriptive-analytical methods, data is collected from various sources, including policy documents. The research results show that although Indonesia has implemented various policies and technologies to improve cyber security, there are still a number of challenges that must be overcome, such as a lack of awareness of cyber threats, limited skilled human resources, and the need for better coordination between relevant institutions. With these steps, it is hoped that cyber security in airspace management can be improved, thereby reducing the risk of attacks and ensuring the safety and efficiency of flight operations in Indonesia.